2000
DOI: 10.1016/s0014-2921(99)00047-1
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity and wage undercutting

Abstract: It is well-documented that employers refuse to hire workers who offer their services at less than the prevailing wage. The received explanation is that workers are motivated by reciprocitythey desire to reward kindness and punish hostility. To refuse an outsider's under-bid is viewed as a kind choice that is met with good effort; a low wage is viewed as an insult that is met with shirking. We have developed a general theory of reciprocity which in this paper is applied to a wage-setting game played by an empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…Positive reciprocity refers to cooperative responses while negative reciprocity refers to retaliatory responses (Fehr and Gächter (2000)). The model that Leuven et al (2005) use represents an adjustment to an earlier reciprocity theory of Dufwenberg and Kirchsteiger (2000). That model shows that a firm's investment in general training may be affected by a worker's sensitivity with respect to reciprocity.…”
Section: Iib Personality Traits and Training Participationmentioning
confidence: 99%
“…Positive reciprocity refers to cooperative responses while negative reciprocity refers to retaliatory responses (Fehr and Gächter (2000)). The model that Leuven et al (2005) use represents an adjustment to an earlier reciprocity theory of Dufwenberg and Kirchsteiger (2000). That model shows that a firm's investment in general training may be affected by a worker's sensitivity with respect to reciprocity.…”
Section: Iib Personality Traits and Training Participationmentioning
confidence: 99%
“…manager and shareholder then follow from differences in perceived kindness λ, see below. An alternative approach leading to similar conclusions would be to let Y vary directly with the identity of the other player considered (see Dufwenberg and Kirchsteiger, 2000). Between workers Y can vary to capture heterogeneity in workers' preferences for reciprocation.…”
Section: Appendix a Formal Justification Of The Reciprocity Hypothesismentioning
confidence: 99%
“…Gaechter and Fehr (2002) give a comprehensive overview on gift-exchange-experiments with abstract (merely monetary) effort choice. These results are generally explained by concepts of social preferences like reciprocity (Rabin, 1993;Dufwenberg & Kirchsteiger, 2000) and inequity aversion or fairness (Akerlof, 1982;Falk & Fischbacher, 2006;Fehr & Schmidt, 1999;Bolton & Ockenfels, 2000). Furthermore, a number of real-effort or field experiment studies have shown that the effects mentioned above are also present in more realistic environments (e.g.…”
Section: Introductionmentioning
confidence: 98%